MasteringTM Excel 2003 Programming with VBA. - Hansen, Steven M. (John Wiley & Sons, 2006)
Create Powerful Business Applications with Excel 2003. Excel 2003 is an ideal application development platform for all levels of business needs. If you're an advanced Excel user looking to gain programming experience, or a skilled developer new to Excel or the Excel Object Model, this no-nonsense book teaches you how to build custom applications that can generate substantial time and cost savings for you, your employer, and your customers.